ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN PETANI UBI-UBIAN DI IRIGASI KELURAHAN PASAR SENTRAL KABUPATEN MIMIKA - Yuliana Likerda Tebai; Rosdiana (CV. Adiba Aisha Amira, 2025)
This study aims to determine the level of income of tuber farmers in the Irrigation of Pasar Sentral Village, Mimika Regency, which is already relatively high when viewed from the cost of production and production results and the influence of production costs, land area, and production results partially and simultaneously on the income of tuber farmers in the Irrigation of Pasar Sentral Village, Mimika Regency. The method used in this study is the descriptive and associative method. Data collection techniques used by researchers are observation, documentation and distributing questionnaires to 21 respondents. The analysis tool used in this study is multiple linear regression analysis. The results of the study indicate that the net income of tuber farmers in the Irrigation of Pasar Sentral Village, Mimika Regency is still relatively low. Perially, production costs have a significant effect on the income of tuber farmers, land area does not have a significant effect on the income of tuber farmers and production results do not have a significant effect on the income of tuber farmers, while simultaneously production costs, land area and production results have a significant effect on the income of tuber farmers in the Irrigation of Pasar Sental Village, Mimika Regency.